Revolutionizing Hotel Room Comfort: Leveraging Google Nest Intelligent Systems to Improve Guest Experience - Suharto, Bambang; Putri, Nabilah Paramita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Technological advances have brought significant changes to the hospitality industry, especially in efforts to improve guest comfort and experience. One of the latest breakthroughs is the use of intelligent systems such as Google Nest to manage the hotel room environment, making it a Smart Hotel Room. This research aims to discuss how the use of Google Nest has revolutionized hotel room comfort and substantially improved the guest experience. Google Nest enables hotels to manage energy efficiently, regulate room temperature, and provide guests with a more personalized experience. We'll discuss some of the benefits of using Google Nest for hotel room comfort, such as better temperature control, better energy management, better security, and integration with property management systems to increase operational efficiency. This research approach uses qualitative methods through analysis of various journals. The results of this research demonstrate a better understanding of how intelligent systems like Google Nest have revolutionized hotel room comfort and substantially improved the guest experience. With thoughtful and innovative implementation, hotels can continue to leverage this technology to create better lodging environments in the future.